Statistical inference for zero-and-one-inflated poisson models - Yincai Tang; Wenchen Liu; Ancha Xu (Statistical Theory and Related Fields, 2017)
In this paper, a zero-and-one-inflated Poisson (ZOIP) model is studied. The maximum likelihood estimation and the Bayesian estimation of the model parameters are obtained based on data augmentation method. A simulation study based on proposed sampling algorithm is conducted to assess the performance of the proposed estimation for various sample sizes. Finally, two real data-sets are analysed to illustrate the practicability of the proposed method.